Sustainable Development in Academic Environment - Šprajc, Polona; Bergoč, Zala; Črnjar, Kristina (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
In this paper, we want to present the field of sustainable development in relation to academia. From a sustainability point of view, the academic environment, like any other environment, is all the more under scrutiny because it does not educate but presupposes knowledge at the highest pillars of education. As such, the importance of the knowledge and competences of graduates is seen as the highest level of responsibility for academic staff. In the context of the trends of the times we live in, sustainability is a constant that means making a contribution today, for tomorrow. And if anywhere, in the academic environment, the importance of knowledge is assumed to mean the well-being of graduates for tomorrow's environment. In the same way, digitalisation is a serious companion to the implementation of sustainability issues in the academic environment, which is why we present this framework in this paper.